Efforts To Improve Children's Fine Motor Abilities Through The 4d Straw Building Game: Classroom Action Research at RA Atta'awun - Herlina Nurhayati; Herminatin (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the fine motor skills of early childhood through the use of the 4D Straw Building game media. The subjects in this study were group A children aged 4-5 years at RA. ATTA'AWUN, Cileunyi District, Bandung Regency, totaling 13 children. The problem underlying this study is the low fine motor skills of children, which can be seen from their difficulties in activities such as holding crayons, using scissors, and other activities that require strength and coordination of the fingers. This study uses the Classroom Action Research (CAR) method of the Kemmis and McTaggart model which is carried out in two cycles. The data collection techniques used are observation and documentation. In the first cycle, the results showed that children's fine motor skills were still low with a development percentage of only 30.8%. After reflection and improvement in the second cycle, there was a significant increase of up to 84.6%. The 4D Straw Building game has proven to be effective in stimulating fine motor development because it involves activities such as holding, pressing, connecting, and forming straws into various creative shapes. In addition, this media also supports the development of children's imagination and creativity in a fun learning atmosphere. The results of this study provide practical benefits for teachers and PAUD institutions in developing innovative and fun learning methods. It can be concluded that the use of the 4D Straw Building game is an effective alternative media to improve fine motor skills in early childhood, and can be applied in daily learning activities in PAUD classes on an ongoing basis.